2005
DOI: 10.1007/s00011-005-1387-0
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of regulatory B cells increases allergic airway inflammation

Abstract: Objective-To investigate the effect of the X-linked immunodeficiency (Xid) B cell defect on the response to the cockroach allergen in mice.Methods-Two cockroach allergen immunization and challenge protocols were employed to sensitize CBA/J wild-type and CBA/CaHN-btk(−/−)xid/J (Xid) mice. Blood and tissue samples were collected 24 and 48 hrs after the last intratracheal antigen challenge and were analyzed for several parameters of allergic inflammation.Results-Nearly equivalent amounts of serum IgE were detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 53 publications
5
41
0
Order By: Relevance
“…Despite resolution of the airway eosinophilia, we have observed persistent expansion of T and B lymphocytes in bronchoalveolar lavage (BAL) fluid and regional hilar lymph nodes (HLN) from mice with LIT (2,3). Other investigators have implicated putative Breg cells in the development of nasal tolerance to aeroallergens (20) and in the suppression of AAD (21). Therefore, the purpose of this study was to investigate the role of B cells in the resolution of AAD and induction of LIT in this OVA model.…”
mentioning
confidence: 89%
“…Despite resolution of the airway eosinophilia, we have observed persistent expansion of T and B lymphocytes in bronchoalveolar lavage (BAL) fluid and regional hilar lymph nodes (HLN) from mice with LIT (2,3). Other investigators have implicated putative Breg cells in the development of nasal tolerance to aeroallergens (20) and in the suppression of AAD (21). Therefore, the purpose of this study was to investigate the role of B cells in the resolution of AAD and induction of LIT in this OVA model.…”
mentioning
confidence: 89%
“…10,11 This was first demonstrated in respective mouse models, where absence of B cells led to an exacerbated course of diseases such as autoimmune encephalomyelitis, chronic colitis, schistosoma infection, and allergy. [12][13][14][15] Further research revealed different potential mechanisms, among them signaling via Fc␥R, 13,14 down-regulation of Th1 response, 16,17 production of immunosuppressive cytokines, [18][19][20][21] and induction of Tregs. 22,23 Unfortunately in many of these in vivo mouse models, "thirdparty" effects, for example, via dendritic cells could not always be excluded.…”
Section: Introductionmentioning
confidence: 99%
“…B-cell antigen presentation is becoming increasingly recognized as an important contributor to disease pathogenesis. 4,[48][49][50] Previous studies using mMT mice in an asthma model have suggested that B cells help to mediate Th2 responses. Using a cockroach antigen model, Lindell et al 4 reported a 50% decrease in Th2 cytokines in the absence of B lymphocytes.…”
Section: Fungal Conidia Inhalation Significantly Increases Collagen Dmentioning
confidence: 99%
“…B cells might have a regulatory role in allergic asthma 4,50,51 or indirectly influence the T-cell response through the alteration of DC function and/or lymph node organization, modifying the resulting phenotype of the response. 48,49,52 In the current study, we demonstrate an expanded role for B lymphocytes in regulating inflammation in the allergic lung.…”
Section: Fungal Conidia Inhalation Significantly Increases Collagen Dmentioning
confidence: 99%